Struktur Komunitas Lamun di Pantai Keranji, Desa Paremas, Kecamatan Jerowaru, Kabupaten Lombok Timur - Syawal, Abdul Syafiq; Aprilya, Nabilah; Rahfika; Buhari, Nurliah; Damayanti, Ayu Adhita; Lestariningsih, Wiwid Andriyani; Rahman, Ibadur (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2024)
Seagrasses are higher plants that grow in marine intertidal areas. Seagrass ecosystems are currently experiencing damage or degradation. The purpose of this study was to assess the structure of seagrass communities in Keranji Beach, Paremas Village. This research was conducted in April 2024, in Paremas Village, East Lombok. The method used was the quadrant line transect method measuring 50×50 cm2 with three transects. The results of this study showed that seagrass health in the research location was in the unhealthy category when viewed through an average cover value of 12.12%. The water quality of Keranji Beach is normal for the growth of seagrass species found, namely Enhalus acoroides, and potential for the life of associated biota.